Translation Priming Effect in Spanish-English Bilinguals - Ramírez Sarmiento, Albeiro (GIST – Education and Learning Research Journal, 2011)
This article aims to establish the effects of masked priming by translation equivalents in Spanish-English bilinguals with a high-intermediate level of proficiency in their second language. Its findings serve as evidence to support the hypothesis that semantic representations mediate the mental association among non-cognates from a speaker’s first and second languages as proposed by Grainger and Frenck-Mestre (1998) in their article entitled “Masked Priming by Translation Equivalents in Proficient Bilinguals.” The present article reports the results obtained from a graduation thesis3 written as a requirement for the M.A. degree in Linguistics at Universidad Nacional de Colombia. This project was finished in 2009 and was funded by the Unit of Research Administration from the School of Human Sciences at Universidad Nacional de Colombia, Sede Bogotá, through the contest “Convocatoria de Apoyo a Trabajos de Posgrado 2008-II”.